Crisis Management Aspects of Bam Catastrophic Earthquake: Review Article - Homayoun Sadeghi-Bazargani; Saber Azami-Aghdash; Abdolhassan Kazemi; Behrad Ziapour (Tabriz University of Medical Sciences, 2015)
Background: Bam earthquake was the most catastrophic natural disasters in recent years. The aim of this study was to review different aspects of crisis management during and after the catastrophic earthquake in Bam City, Iran.Methods: Data needed for this systematic review were collected through searching PubMed, EMBASE and SID databases, for the period from 2003 to 2011. Keywords included earthquake, Iran and Bam earthquake. The data were summarized and were analyzed using Content Analysis.Results: Out of 422 articles, 25 articles were included in the study. Crisis Management aspects and existing pitfalls were classified into seven categories including planning and organization, human resource management, management of logistics, international humanitarian aids, field performance of the military and security forces, health and medical service provision, and information management. Positive aspects and major pitfalls of crisis management have been introduced in all the mentioned categories. Conclusion: The available evidence indicated poor crisis management during Bam earthquake that resulted in aggravating the losses as well as diminishing the effect of interventions. Thus, concerning the importance of different aspects of the crisis management and the high prevalence of disasters in Iran, the observed vulnerability in disaster management process should be addressed.